2012
DOI: 10.1111/j.1741-2358.2010.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and oral health among subjects aged 75 years or older

Abstract: Among the elderly aged 75 years or older, patients with Alzheimer's disease or other types of dementia are at increased risk of poor oral health and poor oral hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 25 publications
9
155
0
8
Order By: Relevance
“…Age-related, mostly chronic pathologies, as well as physiological ageing, will also have to be considered in preventive oral healthcare in this vulnerable population. Institutionalised elderly people, especially those with cognitive impairment, generally have more a compromised oral health, including fewer teeth, than their peers who live independently 3,11 . When assistance is necessary for performing the ADL, oral hygiene is often neglected.…”
Section: Oral Health In Old Agementioning
confidence: 99%
“…Age-related, mostly chronic pathologies, as well as physiological ageing, will also have to be considered in preventive oral healthcare in this vulnerable population. Institutionalised elderly people, especially those with cognitive impairment, generally have more a compromised oral health, including fewer teeth, than their peers who live independently 3,11 . When assistance is necessary for performing the ADL, oral hygiene is often neglected.…”
Section: Oral Health In Old Agementioning
confidence: 99%
“…A study from Finland reported that patients diagnosed with dementia by a geriatrician, but excluding AD, had an increased likelihood of periodontal infections (Syrjala et al 2012); however, the number of dentate individuals studied was small and periodontal infection was equated with the presence of pocketing of 4 mm. A further recent European study of 152 dentate 70-year-old subjects in Denmark found that those with periodontal inflammation had lower scores in tests of cognitive function (Kamer et al 2012).…”
Section: Commentmentioning
confidence: 99%
“…They were conducted in 5 different countries across Europe [10,12] , North [26] and South America [27] , and Asia [11] , and were published between 1994 and 2015 ( Table 1 ). The population sample ranged from 42 patients in the study by Ship and Puckett [26] to 409 patients in the study by Gil-Montoya et al [12] 2 of the studies were cross-sectional [10,11] , 2 were case-control [12,27], and one was a longitudinal observational study [26] .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…In the previous years, there has been an increase in the publication of literature in order to investigate the possible association between PD and AD, with heterogeneous results [10][11][12] . Despite the existence of numerous narrative reviews [8,9,[13][14][15][16] , the use of subjective and non-standardized methods may have led to bias [17] .…”
Section: Introductionmentioning
confidence: 99%